Antioxidant study of pulp and peel of dragon fruits: A comparative study - Ruzlan, Nurliyana; Kamarudin, Kamarul Rahim; Syed Osman Idid, Syed Zahir Idid; Mohamed Rehan, Aisyah; Koya, Mustapha Suleiman (2008)
Dragon fruit is one of the tropical fruits that are believed rich in antioxidant. Nevertheless, to date little is known regarding their antioxidant potential. In accordance with the natural colours of dragon fruits, the fruits may be rich in phytonutrients that play main roles in antioxidant activity. Two species of dragon fruits, Hylocereus undatus (white dragon fruit) and Hylocereus polyrhizus (red dragon fruit) were used as model systems in this study. Peels and pulps of both Hylocereus species were separated before being extracted using 70% ethanol. Total phenolic content (TPC) assay was performed to determine the level of phenolic presence using Folin-Ciocalteu’s assay. Determination of primary and secondary antioxidant activities for both species were evaluated using 2, 2, diphenyl-1-picrylhydrazyl (DPPH) assay and ferrous ion chelating (FIC) assay. The results demonstrated that the peels contained higher amount of phenolic compound compared to the pulps. In comparison between the peels of both species, it showed that peel of H. undatus possessed higher phenolic content than H. polyrhizus. The pulp of H. polyrhizus contained around 197.15 mg/L of phenolic compound, whereas H. undatus puls contained as low as 37.46 mg/L of phenolic compound. Radical scavenging activity of the peels for both species was higher than the pulps. Both peels of Hylocereus species showed high percentage of scavenging activity that reached up to 87%. However, scavenging activity for the pulp of H. undatus was lower than H. polyrhizus. Furthermore, both peels and pulps of Hylocereus species showed weak metal ion chelating effect as compared to EDTA. It was found that pulp of both species showed a significant secondary antioxidant effect instead of primary antioxidant effect. Overall, since the results showed that peels and pulps of H. undatus and H. polyrhizus possessed potent antioxidant capacity, dragon fruits can be considered as potential natural antioxidant source which can be utilized in relevant industries.